Manajemen Pembelajaran Matematika - Manullang, Martua (Jurnal Pendidikan Matematika dan Sains, 2017)
The article was written as a response to the fact that the quality of mathematic teaching and learning is still relatively low. Teachers play an important role in determining the quality of education, because teachers are in the frontline of the whole education process. This article offers a solution so that teachers are aware of the importance of the understanding of management in the teaching plan. Based on theoretical study concerning the management application in the development of mathematic lesson plan and the Government Regulation No 14/2005 article 8 as well as the statute of the Directorate of Teaching Profession, the presence of lesson plan in every process of teaching and learning is required by the system and is a part of learning management.